Uptake and reduction of nitrate in two rice cultivars in the presence of aluminum - Justino, Gilberto Costa; Cambraia, José; Oliva, Marco Antonio; Oliveira, Juraci Alves de (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effects of Al on the nitrate uptake and reduction in two rice cultivars, Fernandes (Al tolerant) and Maravilha (Al sensitive), exposed to 0 and 500 µM Al. After 21 days of Al treatment, growth in size and dry matter yield, Al and nitrate contents and in vitro nitrate reductase activity (NR) in the tops and roots, and the kinetic constants of root nitrate uptake were determined. Aluminum reduced the growth and dry matter yield of both plant parts only in the Maravilha cultivar. Aluminum content increased in the tops and roots of both cultivars, while nitrate content decreased only in the roots of Maravilha cultivar. Vmax did not change, while Km of the nitrate uptake decreased in Fernandes by 11% and increased about 310% in Maravilha cultivar. In the presence of Al the NR activity decreased in the roots of both cultivars, and in the leaves of Maravilha cultivar. The Al tolerant cultivar was more efficient in nitrate absorption and reduction, wich indicates that these processes could be important components of Al tolerance in rice.